The Right to Excellence Illumination and Human Rights - منوچهری, عباس (جاویدان خرد, 2022)
In the classical Greek thought, the notion of “right” was concomitant with the “truth”. In the modern era, however, the notion of “right” became intertwined with the primacy of   “possessive individuality”. This primacy was, however, from the outset intellectually challenged. In the light of challenges posed, and by invoking the commonalities between Shahaboddin Suhrawardi and Martin Heidegger, the right to excellence is envisioned here as a maximal theory of “human rights”.